Physical and Chemical Strategies for Therapeutic Delivery by Using Polymeric Nanoparticles - Morachis, José M. (The American Society for Pharmacology and Experimental Therapeutics, 2012)
A significant challenge that most therapeutic agents face is their inability to be delivered effectively. Nanotechnology offers a solution to allow for safe, high-dose, specific delivery of pharmaceuticals to the target tissue. Nanoparticles composed of biodegradable polymers can be designed and engineered with various layers of complexity to achieve drug targeting that was unimaginable years ago by offering multiple mechanisms to encapsulate and strategically deliver drugs, proteins, nucleic acids, or vaccines while improving their therapeutic index. Targeting of nanoparticles to diseased tissue and cells assumes two strategies: physical and chemical targeting. Physical targeting is a strategy enabled by nanoparticle fabrication techniques. It includes using size, shape, charge, and stiffness among other parameters to influence tissue accumulation, adhesion, and cell uptake. New methods to measure size, shape, and polydispersity will enable this field to grow and more thorough comparisons to be made. Physical targeting can be more economically viable when certain fabrication techniques are used. Chemical targeting can employ molecular recognition units to decorate the surface of particles or molecular units responsive to diseased environments or remote stimuli. In this review, we describe sophisticated nanoparticles designed for tissue-specific chemical targeting that use conjugation chemistry to attach targeting moieties. Furthermore, we describe chemical targeting using stimuli responsive nanoparticles that can respond to changes in pH, heat, and light.